Some numerical aspects of modelling flow around hydraulic structures using incompressible SPH. (June 2015) - Ghadampour, Z.; Hashemi, M.R.; Talebbeydokhti, N.; Neill, S.P.; Nikseresht, A.H.
Abstract Here, we apply incompressible smoothed particle hydrodynamics (ISPH) to simulate free-surface flow around hydraulic structures using several classical case studies including dambreak, flow under a submerged gate, and simultaneous operation of a weir and gate. Due to many complexities such as unknown free-surface, rapidly varied flow, trans-critical flow, complicated geometry, and non-hydrostatic pressures, flow fields have traditionally been investigated by experimental methods, while powerful computational techniques such as ISPH are gradually being adopted for such studies. This research provides further details about the application of ISPH in this area. Two projection methods to enforce incompressibility of SPH were compared from mathematical and numerical view points. Further, two pressure formulations for approximating the left-hand-side of the Poisson equation resulted in a similar trend.